Directional white-light emission from sintered carbon dot titanium dioxide structures based on near-field confinement - Dalei Wang; Xiaoxia Han; Hao Wang; Zenan Li; Zhaomin Chen; Qing Yang; Mingcheng Yang; Zexin Zhang; Yizhi Zhu; Jintao Tong; Jie Lin; Jingsong Huang; et al. (Nature Communications)
Abstract Directional light source not only helps to advance scientific progresses but also has great potentials in many application fields. However, it is still challenging to achieve the directional white light without optical elements. Here, we report a highly directional white-light emitter driven by 1064 nm near-infrared laser with 1/60 solid angle that does not require the introduction of optical elements. The emitter which consists of binary components, i.e. carbon dot and titanium oxide, possesses a microlens-shape surface formed during the synthesis process. Upon near-infrared light excitation, carbon dot emits white light based on a fundamentally different mechanism, which may involve a process similar to bremsstrahlung, multiphoton and thermal processes. The emitted white light is then regulated in the near field by the microlens-shape surface due to the confinement effect, resulting in the high directionality. The highly directional white-light emitter exhibits excellent stability and repeatability, making it promising for applications including targeted illumination and projection.